Strategi Komunikasi Pondok Pesantren dalam Pembinaan Karakter Santri: Studi Kasus Pondok Pesantren Miftahul-Huda Bogor - Noor Fadhiilah, Muhammad; Basri Tanjung, Hasan; Fahmi Irfani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
Communication in the world of education and learning is a very important element and has a big role for success in the process of teaching and learning activities in the classroom. The role of communication between teachers and students in pesantren, this communication must also use clear language. Character building in boarding schools through a good and consistent environment plays an important role in shaping the character of good students for the future. As for 1). To find out the communication strategy in fostering character in students of Miftahul-Huda Islamic Boarding School Bogor. 2). To find out the supporting and inhibiting factors in the application of character building for students of Miftahul-Huda Islamic Boarding School Bogor. The research method used is a qualitative method with data collection techniques used are in-depth interview techniques and documentation. The analysis technique uses data reduction analysis, data presentation, conclusion drawing, and verification. The results of this study show first that the communication strategy in fostering the character of students can be seen from special programs (Tahsin and tahfidz, Yellow Book Studies and Foreign Languages). Second, the supporting factors are: Infrastructure facilities and education management of Miftahul-Huda Islamic Boarding School in Bogor. The inhibiting factors for the implementation of santri character development through communication strategies, namely: The background of the students, the educational background of the students and the ability of the students to understand the learning at the Miftahul-Huda Islamic Boarding School in Bogor.